Synthesis of metallic aluminum particles by electrolysis in aqueous solution - Takefumi Hosoya; Takehiro Yonezawa; Noriko Yamauchi; Kouichi Nakashima; Yoshio Kobayashi (Micro and Nano Systems Letters, 2021)
Abstract The present work proposes a method for fabricating metallic Al particles in aqueous solution. An aqueous colloidal solution was prepared from an aqueous aluminum nitrate nonahydrate solution by electrolysis using metallic Al plates as the anode and cathode under ultrasonic irradiation in water at 25–45 °C. The sizes of the particles in the colloidal solutions prepared at 25, 35, and 45 °C were 76.3, 77.0, and 84.7 nm, respectively. The powder obtained from the colloidal solution prepared at 25 °C was not crystalline. By contrast, the powders obtained from the colloidal solutions prepared at 35 and 45 °C had a crystal structure of cubic Al and crystal sizes of 55.7 and 59.3 nm, respectively. Thus, elevated temperatures promoted both particle growth and crystal growth, which was explained by higher temperatures increasing the frequency and energy of particle collisions. The metallic Al particles were chemically stable in both an aqueous solution and the ambient atmosphere. The chemically stable metallic Al particles are expected to be used as sources for fabricating materials related to fuels, energy storage, and pigments.